Experimental Evaluation of a SIP-Based Home Gateway with Multiple Wireless Interfaces for Domotics Systems - Garroppo, Rosario G.; Gazzarrini, Loris; Giordano, Stefano; Tavanti, Luca (Journal of Computer Networks and Communications, 2012)
In modern houses, the presence of sensors and actuators is increasing, while communication services and entertainment systems had long since settled into everyday life. The utilization of wireless communication technologies, such as ZigBee, Wi-Fi, and Bluetooth, is attractive because of their short installation times and low costs. The research is moving towards the integration of the various home appliances and devices into a single domotics system, able to exploit the cooperation among the diverse subsystems and offer the end-user a single multiservice platform. In this scenario, the paper presents the experimental evaluation of a domotics framework centered on a SIP-based home gateway (SHG). While SIP is used to build a common control plane, the SHG is in charge of translating the user commands from and to the specific domotics languages. The analysis has been devoted to assess both the performance of the SHG software framework and the negative effects produced by the simultaneous interference among the three widespread wireless technologies.